The challenge of local culture representation in the movie "Welcome to Jogja" - Khozinatul Asror; Vani Dias Adiprabowo (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
The Special Region of Yogyakarta is renowned for its rich cultural heritage and historical significance in Indonesia. It is also a source of inspiration for numerous cinematic works. Despite the abundance of films depicting Yogyakarta, previous studies have not thoroughly elucidated its cultural significance. This research employs a qualitative methodology to examine the cultural elements of Yogyakarta as portrayed in the film "Welcome to Jogja." The objective of this study is to explore the cultural values of Yogyakarta as implied in the film. The data collection methods included observation, documentation, and a literature review of prior research. This study identifies and analyzes the representation of Yogyakarta's cultural values as reflected in the film "Welcome to Jogja." The findings indicate that the film offers a comprehensive depiction of Mataraman Javanese culture through visual and symbolic elements such as lurik clothing, dance, jemparingan, Labuhan Parangkusumo rituals, karawitan, and batik. These cultural icons are presented through props and courtyard designs. The film not only showcases the aesthetic beauty of Javanese culture but also invites the audience to comprehend the profound meanings underlying it all. Consequently, this research contributes to the understanding and appreciation of Yogyakarta's cultural richness and promotes regional cultural heritage in the film industry context.   Daerah Istimewa Yogyakarta merupakan salah satu kota di Indonesia yang terkenal dengan kekayaan budaya dan sejarahnya. Yogyakarta juga diketahui sebagai kota yang menjadi sumber inspirasi berbagai karya film. Oleh karena banyaknya film mengenai Yogyakarta pada beberapa kajian sebelumnya tidak secara kompherensif menjelaskan budaya Yogyakarta. Melalui pendekatan kulaitatif, penelitian ini akan menguraikan mengenai beberapa budaya di Yogyakarta yang ada pada Film “Welcome to Jogja”. Penelitian ini bertujuan untuk menggali nilai budaya Yogyakarta yang tersirat dalam film tersebut. Dengan pengumpulan data melalui observasi, dokumentasi dan studi literatur berdasar penelitian terdahulu, penelitian ini mengidentifikasi dan menganalisis representasi nilai budaya Yogyakarta yang tercermin dalam film "Welcome to Jogja". Hasil penelitian menunjukkan bahwa film ini menghadirkan representasi budaya Jawa Mataraman yang kaya melalui elemen visual dan simbolis seperti baju lurik, tari, jemparingan dan ritual Labuhan Parangkusumo, karawitan, membatik. Ikon visual tersebut muncul dalam bentuk properti dan desain pelatarannya. Film ini tidak hanya memperlihatkan keindahan budaya Jawa, tetapi juga mengajak penonton untuk memahami makna mendalam di baliknya. Dengan demikian, penelitian ini memberikan kontribusi dalam memahami dan menghargai kekayaan budaya Yogyakarta, serta mempromosikan warisan budaya daerah dalam konteks industri perfilman.